2022
DOI: 10.1161/jaha.121.023845
|View full text |Cite
|
Sign up to set email alerts
|

Association of Accelerometer‐Measured Sedentary Accumulation Patterns With Incident Cardiovascular Disease, Cancer, and All‐Cause Mortality

Abstract: Background Emerging evidence suggests accruing sedentary behavior (SB) in relatively more prolonged periods may convey additional cardiometabolic risks, but few studies have examined prospective outcomes. We examined the association of SB accumulation patterns with incident cardiovascular disease (CVD), cancer, and all‐cause mortality (ACM). Methods and Results Data were from 7671 EPIC‐Norfolk (European Prospective Investigation Into Canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 51 publications
(114 reference statements)
0
18
1
Order By: Relevance
“…Three studies found no association between total time spent in SB or SB accumulation patterns with CVD risk after adjustment for covariates. 14 , 22 , 28 Null findings may be due to inadequate power 28 or the use of uniaxial accelerometers, which may not be as precise in measuring SB. 15 In contrast, 5 other studies reported that greater daily sedentary time was associated with increased risk of total CVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies found no association between total time spent in SB or SB accumulation patterns with CVD risk after adjustment for covariates. 14 , 22 , 28 Null findings may be due to inadequate power 28 or the use of uniaxial accelerometers, which may not be as precise in measuring SB. 15 In contrast, 5 other studies reported that greater daily sedentary time was associated with increased risk of total CVD.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 , 16 , 17 , 18 , 19 , 23 , 24 , 25 , 26 Moreover, although there is strong evidence for an association between self‐reported SB and CVD incidence, 11 there is mixed evidence for whether accelerometer‐measured SB is associated with an increased risk of CVD or CVD mortality. 14 , 15 , 16 , 18 , 22 , 24 , 25 , 27 , 28 Public health interventions that increase time spent in higher‐intensity activities inherently require spending less time in a lower‐intensity activity, as time is fixed within a day. Few studies have assessed whether substituting time spent sedentary for either HLPA or MVPA, measured by accelerometry, is associated with lower risk of CVD.…”
mentioning
confidence: 99%
“…Analysis of accumulation pattern showed that EMG inactivity duration was accumulated through shorter EMG inactivity bouts, the lower the EMG inactivity threshold was (median 1 second to 97 seconds). Accelerometer-measured usual sedentary bout duration has been reported to be around 17-26 minutes in healthy participants, and several studies have reported that accruing total sedentary time in longer sedentary bouts is adversely associated with health [5][6][7][8][9]49 . However, in one study also short sedentary bouts were found to be detrimental 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Observational evidence has further indicated that total overall volume of sedentary time is associated with incident of cardiovascular diseases and all-cause mortality 3,4 . In addition, accumulating sitting time or sedentary time in a prolonged unbroken manner consistent with long periods of muscle inactivity is associated with markers of cardiometabolic health, prevalent diabetes, incident cancer and all-cause mortality [5][6][7][8][9] . While high total sedentary time and a prolonged pattern of accumulation often co-exist, they may carry partly independent, and/or additive risk for health 5,6,10 .…”
Section: Introductionmentioning
confidence: 99%
“…12 Using accelerometers, bouts of activity and sedentary behavior can be calculated in many ways, such as activity fragmentation, active and sedentary bout length, or interruptions of a sedentary bout per hour. 8,[13][14][15][16][17] Activity fragmentation calculates the probability of transitioning from active to a sedentary state using minute-byminute data. 8 Active and sedentary bout length captures accumulation of these activities in specified bout lengths (e.g., accumulation of active bouts lasting 2-4 min, etc.).…”
Section: Introductionmentioning
confidence: 99%